Molecular prevalence and haplotype diversity of tick-borne haemopathogens in shelter dogs in Peninsular Malaysia - Sipin, Quincie (2020)
Canine tick-borne haemopathogens (TBH) constitute a significant concern worldwide and warrant closer surveillance due to their zoonotic potential. Infection in dog is a reliable indicator for infection risk in a certain geographical area. The detection of these TBHs is mainly achieved by microscopic evaluation, seroprevalence, and molecular detection. Although molecular detection was used in recent studies, the studies were limited to the central region and certain main cities in Peninsular Malaysia. Additionally, there is scarce information on molecular detection of the haemopathogens in the vector infesting dogs in Peninsular Malaysia. Detailed research is imperative to demonstrate the host-vector interaction between the animal host (dog) and arthropod vector (Rhipicephalus sanguineus (R. sanguineus tick)) for the transmission of TBHs of dogs in Peninsular Malaysia. Therefore, the present study was designed to investigate the molecular detection of TBHs in shelter dogs and their ticks in Peninsular Malaysia, as well as to determine the pattern of haplotype separation between TBHs in dogs and their ticks. A total of 220 dogs’ blood and 140 R. sanguineus ticks were collected from animal shelters in Peninsular Malaysia during the study. The presence of haemopathogens in blood and tick samples was detected using conventional PCR, sequenced, and identified at the species level. Ehrlichia canis (E. canis) was detected from dogs and ticks with detection rates of 20% (n=43) and 1.43% (n=2), respectively. On the other hand, 12% (n=26) of the dogs and 1.43% (n=2) of the ticks were tested positive for Anaplasma platys (A. platys). Babesia gibsoni (B. gibsoni) was only detected in dogs (7%; n = 16), whereas Babesia vogeli (B. vogeli) was detected in both tick (0.71%; n=1) and dogs (7%; n=16). Male and young dogs showed significantly higher A. platys and B. vogeli infection rates (p<0.05), respectively. Up to triple infections of haemopathogens observed in the sampled dogs but no co-infection of TBHs in ticks obtained in the present study. The haplotype network analysis results revealed no specific pattern or separation between isolates of TBHs in dogs and ticks from different region, since samples collected from different region were observed clustered together in the same haplotypes, thus were not able to demonstrate the pattern of canine TBHs transmission in Peninsular Malaysia. However, the study revealed a higher haplotype and nucleotide diversities when using mitochondrial gene marker compared to nuclear gene marker, which will be useful in exploring variation in population of parasites. The findings obtained in the present study contribute to a more comprehensive information on the prevalence and distribution of TBHs in shelter dogs and their ticks in Peninsular Malaysia, as well as providing basic knowledge on the molecular variation of TBHs isolates in Peninsular Malaysia as baseline for future molecular characterisation studies.